The use of semi-syntetic casings in tulum cheese production and effects of vacuum packaging on quality - O. Cenap Tekinşen; Mustafa Nizamlıoğlu; Abdullah Keleş; Mustafa Atasever; Ahmet Güner (Eurasian Journal of Veterinary Sciences)
Experimental tulum cheese samples were produced according to the traditional method. The use of synle-tic packaging materials and the effects of vacuum packaging on the quality properties were investigated. It is concluded that syntetic casings can be used as a packaging material for the tulum cheese. But cheese should be stored in the conditions of having high relalive humudity. As vacuum packed samples had better in chemical, microbiological and sensory properties than the non-vacuumed ones, vacuum packaging can also be used effectively in packing the tulum cheese.